THE ROLE OF DAYAH BABUL HUDA IN RELIGIOUS DEVELOPMENT IN COMMUNITIES IN JAYA DISTRICT ACEH JAYA DISTRICT - Isa, M.; Azmi, Ulil; Baihaqi, T. (Journal of Learning on History and Social Sciences, 2024)
In fostering religious education in the community in Jaya District, Aceh Jaya Regency, Dayah Babul Huda continues to strive to play its important role in increasing religious awareness and understanding in the community through preaching and education. However, to optimize the coaching program, strategic steps are needed, such as improving facilities and infrastructure, stronger financial support, and adjusting learning methods to be more relevant to current developments. This research method uses qualitative research with a field research approach. The data sources are the leaders of Islamic boarding schools and local community leaders. The results of the study show that 1). The role of Dayah Babul Huda in increasing religious awareness and understanding of the community in Jaya District, Aceh Jaya Regency is very significant. With a structured religious education program, consistent preaching, and spiritual guidance provided, Dayah Babul Huda has succeeded in fostering the community to better understand and practice Islamic teachings. 2). The challenges faced by Dayah Babul Huda in providing religious guidance to the community include limited physical facilities, differences in the level of community understanding, the influence of technology and social change, limited number of teachers, and financial constraints